Produção e caracterização de esferas de TiO2/Alumina para utilização em fotocatálise heterogênea - Lima, Ediano Duarte de (2018)
With the increasing pollution of water bodies, due mainly to industrial development, water quality has been increasingly being discussed by researchers around the world, since conventional treatments do not remove substances of difficult degradation discarded every day in a way uncontrolled and without any concern. Among these pollutants we can mention among others the industrial solvents, which can aggravate the water quality even more. Thus, Advanced Oxidative Processes (POA), in particular heterogeneous photocatalysis with TiO 2, have appeared as an excellent alternative for the treatment of residues and recalcitrant organic substances present in aqueous effluents in low concentrations, mainly due to their high efficiency on chemical degradation against resistant substrates. The use of supported photocatalysts has been the preferred strategy in heterogeneous photocatalysis, since the separation of the photoactive material from the reaction medium is difficult and expensive. And the spherical shape is preferably desired because it has the advantage of a better surface characterization, allowing the establishment of geometric parameters useful for reproducibility of the process and for comparisons. In this work, TiO2/Alumina beads were produced for use in heterogeneous photocatalysis. For the preparation of the spheres the method used was the one per drops generation, which consists of the preparation of a gel formed by aluminum hydroxide and TiO2 that was mixed to a viscous solution composed of chitosan (mold) and acetic acid. After complete mixing of the gel and the viscous solution, the precursor solution was obtained to obtain the TiO2/Alumina beads. The precursor solution was dripped into a buffer / coagulation solution composed of a heterogeneous two-phase mixture: a thin layer formed by cyclohexane, which promotes damping of the beads, and the coagulation phase formed by a 50% v/v solution of ammonium hydroxide and distilled water forming the beads. After being produced, the beads were washed, dried and calcined at 700°C. They were characterized by their morphology (MEV and EDS), DRX, mass and volume. The photocatalytic activity of the spheres was evaluated using a photocatalytic reactor constructed to degrade the ionic liquid 1-Ethyl-3-Methylimidazolium chloride [EMIM][Cl]. In the tests, degradations of up to 52.84% were obtained which were monitored by LC-MS. The spheres used in the first cycle were dried, calcined and reused in two more cycles of photodegradation tests without undergoing any cleaning process and maintaining their photocatalytic activity.